PENINGKATAN HASIL BELAJAR SIFAT-SIFAT BANGUN DATAR DENGAN PENDEKATAN CTL DI KELAS V SEKOLAH DASAR - Yusnita, Yosmai Vera; Ahmad, Syafri; Zen, Mulyani (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The aim of the research is to describe the learning outcome of the “shape and space of Geometry” by using Contextual Teaching and Learning Approach at 5th grade of SDN 08 Campago Ipuh, Bukittinggi. The subjects of the research were the teacher and 21 students of the school. The result of the research show that there is an improvement on stundents learning outcome. In cycle I the average score is 72.46%, while in cycle II is 87.75%. thus, the use of Contextual Teaching and Learning Approach has improved the students learning outcome in leraning the topic of shape and space geometry at 5th grade of SDN 08 Campago Ipuh, Bukittinggi.Keywords: Learning outcomes, shape and space of geometry, Contextual Teaching and Learning approaches